PERAN SELF-CONTROL DALAM MEMODERASI HUBUNGAN FEAR OF MISSING OUT DAN KESEJAHTERAAN PSIKOLOGIS MAHASISWA - Rahman, Julia; Nurul Insani, Camelya; Suryandari, Meity (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
Fear of Missing Out (FoMO) has emerged as an increasingly concerning psychological phenomenon among university students as the most active social media users. While the negative relationship between FoMO and psychological well-being has been extensively studied, the role of self-control as a moderator particularly within Ryff's eudaimonic psychological well-being framework in the Indonesian context has not been systematically reviewed. This study aims to conceptually and theoretically examine the role of self-control as a moderator in the relationship between FoMO and psychological well-being among university students, while identifying the novelty and research gaps justifying this study. This study employs a systematic literature review method, identifying, selecting, and synthesizing articles from Google Scholar, PubMed, and PsycINFO published between 2013 and 2024 using keywords FoMO, self-control, psychological well-being, and university students. Review of 28 eligible articles demonstrated: (1) FoMO consistently correlates negatively with student psychological well-being; (2) self-control serves as a protective factor through strengthening self-regulation and preventing compulsive digital behavior; (3) no study has explicitly tested the moderating effect of self-control on the FoMO eudaimonic psychological well-being relationship in Indonesia. There is strong theoretical and empirical justification that self-control can moderate the negative impact of FoMO on student psychological well-being. The novelty of this study lies in integrating three constructs (FoMO, self-control, and Ryff's psychological well-being) into a moderation model not previously tested in the Indonesian cultural context.